How Chinese learn mathematics : perspectives from insiders - Fan, Lianghuo (Series on mathematics education ;, 2004)
The book has been written by an international group of very activeresearchers and scholars who have a passion for the study of Chinesemathematics education. It aims to provide readers with a comprehensiveand updated picture of the teaching and learning of mathematicsinvolving Chinese students from various perspectives, including theways in which Chinese students learn mathematics in classrooms, schools and homes, the influence of the cultural and socialenvironment on Chinese students' mathematics learning, and thestrengths and weaknesses of the ways in which Chinese learnmathematics.